The Role of Teachers In Developing Speech Skills in Speech Delay Childern at Orbit 2 Kindergarten Surakarta - Nurhayati, Umi; Widyasari, Choiriyah (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The study discussed children who had speech delay at the age of 5 years. Where at this age children begin to develop and feel curious to know what they see and listen to. The purpose of this study is to find out how children who have a delay in speech learning. Methodology: The method chosen by the researcher here, namely the qualitative method, is a type of research that explores and understands the meaning in a number of individuals or groups of people who come from social problems. This research method was chosen because it is considered to be able to provide a broader and deeper understanding of the problems raised in this study. Results: From the results of interviews and observations conducted by the researcher to teachers and school principals, the researcher found that there are 5 types of strategies given by teachers to handle children's speech delay: (1) Setting aside a seat for the subject to focus more on learning, (2) teaching children to speak more clearly and correcting errors in pronunciation, (3) providing story books with interesting pictures to tell stories about the subject, (4) inviting children to tell stories , and (5) provide books for coloring. Applications/Originality/Value: This study provides practical strategies for teachers to assist in the development of speech skills in children experiencing speech delay. The research highlights various methods, including seat isolation for better focus, corrective pronunciation practices, use of storybooks, storytelling activities, and coloring exercises. These strategies are directly applicable in early childhood education settings, especially for teachers working with children with special needs, and can help improve the learning environment for children experiencing speech delays.